2013
DOI: 10.5301/ejo.5000286
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma with Unusual Association of Postaxial Polydactyly

Abstract: Postaxial polydactyly should be considered as an association of retinoblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The PAPA2 locus is situated at 13q21‐q32, close to the RB gene locus 13q14.1‐q14.2. Further investigation is required to explore this potential link (Mishra et al., 2013 ). While retinoblastoma is highly curable, it remains fatal if left untreated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PAPA2 locus is situated at 13q21‐q32, close to the RB gene locus 13q14.1‐q14.2. Further investigation is required to explore this potential link (Mishra et al., 2013 ). While retinoblastoma is highly curable, it remains fatal if left untreated.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this case was not subjected to DNA sequencing analysis. In 2013, a study from India reported on an 8‐year‐old boy with retinoblastoma and postaxial polydactyly (Mishra et al., 2013 ). Similarly, the boy had no family history, experiencing vision loss in his left eye.…”
Section: Discussionmentioning
confidence: 99%